2017
DOI: 10.1016/j.jcomm.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the multivariate dynamic dependence structure of commodity futures portfolios

Abstract: This paper examines the time-varying dependence structure of commodity futures portfolios based on multivariate dynamic copula models. The importance of accounting for time-variation is emphasized in the context of the Basel traffic light system. We enhance the flexibility of this structure by modeling regimes with multivariate mixture copulas and by applying the dynamic conditional correlation model (DCC) to multivariate elliptical copulas. The most suitable dynamic dependence model in terms of in-sample and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 66 publications
(62 reference statements)
1
10
0
1
Order By: Relevance
“…The table indicates that the GARCH(1, 1) is the optimal choice overall, and we will continue with this specification. Similar results are found in Paraschiv et al (2015) and Aepli (2011). Table 5 displays the estimated GARCH-GJR parameters.…”
Section: Application Of the Garch-gjrsupporting
confidence: 78%
See 4 more Smart Citations
“…The table indicates that the GARCH(1, 1) is the optimal choice overall, and we will continue with this specification. Similar results are found in Paraschiv et al (2015) and Aepli (2011). Table 5 displays the estimated GARCH-GJR parameters.…”
Section: Application Of the Garch-gjrsupporting
confidence: 78%
“…In McNeil et al (2015) the authors suggested using a combination of GARCH and EVT. This methodology is popular in recent literature, with the largest proportion of new studies focusing on stock markets or single commodities (Ghorbel and Souilmi 2014;Liu 2011;Wang et al 2010;Aepli 2011).…”
Section: Regulatory Requirements For Stress Testingmentioning
confidence: 99%
See 3 more Smart Citations